A novel bidirectional and dual-redundancy hybrid electromagnetic brake for aircraft. (September 2016) - Xiao, Chunyan; Gao, Shuai; Zhang, Jun
This article presents a novel bidirectional and dual-redundancy hybrid electromagnetic brake with strong retention force and high reliability. The electromagnetic brake with two large working air gaps consists of two stationary components and a movable component which is fixed to the shaft. The stationary components are composed of iron cores, yokes, and two sets of coil windings in which one set of redundant ones can improve reliability. The movable component consists of a permanent magnet ring and yokes. When the power is outage, the permanent magnet can provide a constant retention force to keep the movable component park at end position. When the power is on, the working magnetic fluxes of the hybrid electromagnetic brake are generated by both the permanent magnet and the coil windings carrying DC forward or reverse current. The magnetic fluxes produced by coil windings control the movement direction of the movable component to realize braking or unlocking. First, the constraint conditions of magnetomotive force to ensure bidirectional movements were deduced using the equivalent magnetic circuit method. Then, the magnetic flux density and the electromagnetic forces were calculated by the finite element method. Simulation results validated the theoretical analysis and the reasonable design. This electromagnet can be used for the electrical brake not only in the more electric aircraft but also in other applications.